PENGARUH SENAM OTAK TERHADAP MOTORIK HALUS PADA ANAK USIA DINI DI TK MUSLIMAT NU 27 MALANG - Intan Ramadani D.P; Rifzul Maulina; Sulistiyah (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
A person in their early years is going through a crucial developmental stage that will affect them in the future. The aim of this study was to ascertain how early infancy fine motor abilities are affected by brain snam.Pre-experiment with a single group pre-posttest design was used in this study. 22 young children made up the study's population. Using the purposive sampling approach, a sample of eighteen respondents was collected. An observation sheet in the KPSP format was the instrument utilized in this investigation. SPSS16 was used to process the study data that were collected. The study's interpretation of the impact of brain gymnastics on enhancing children's fine motor development is supported by the Wilcoxon Test data, which indicate that the p value ? ? (0.05) is 0.000 <0.05, indicating that H1 is accepted and H0 is rejected. This study's findings indicate that brain gymnastics at TK Muslimat NU 27 Malang, both before and after the intervention, has an impact on young children's fine motor development.